Durability of Modified Fiber Plactic Composite (FPC) Against Marine Borer - Ade Dwi Fonna Rizki; Luthfi Hakim; Ridwanti Batubara (Program studi Kehutanan USU, 2014)
The Fiber plastic composite (FPC) board that made from corrugated paper fiber and plastic polypropylene with maleic anhydride (1 % and 2 %) as compatibilizer and benxzoil peroxide (15 %) as initiator (modified). The purpose of this research were to evaluate the quality of the physical properties of modified FPC board, identification kinds of marine borer, and the durability against marine borer. The physical properties was based on JIS A 5905-2003 and JIS A 5908-2003. The durability of modified FPC board against marine borer was based on SNI 01-7207-2006. The Modified FPC board was soaking in the sea of Port Belawan, Medan for six months.The results showed the physical properties of modified FPC board were full fil the standard JIS A 5905-2003 and JIS A 5908-2003. The durability of modified FPC board against marine borer according SNI 01-7207-2006 was classified into very durable and durable. The marine organism which found on modified FPC board were 17 specieses but only 2 specieses classified as marine borers, there are Limnoria sp and Teredo sp. After the split test was known that the pattern of attacks on the modified FPC board is Martesia striata's attack patterns of pholadidae.Keywords: FPC, Marine Borer, Modified, Physical Properties, Sea Of Port Belawan